Penggunaan Media Papan Berhitung Pada Pembelajaran Matematika Untuk Siswa Kelas II SDN 6 Wonogiri - Ratana, Bodhi (Pendidikan Dasar dan Manajemen Pendidikan, 2023)
Mathematics is a natural science that has an important role in the development of science and technology. Many learners in school view maths as the most difficult subject. In fact, until now there are still students who are less interested in mathematics and the results of learning mathematics have not shown optimal results. This type of research is Research and Development (R&D), which is research to produce new products or perfect existing products. that the counting board product is "Very Feasible" to use, so it can be concluded that the counting board media product is effectively used as a mathematics learning medium in grade II SD Negeri 6 Wonogiri